2016
DOI: 10.1016/j.neuropsychologia.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition processes are dissociable and lateralized in human prefrontal cortex

Abstract: The prefrontal cortex (PFC) is known to make fundamental contributions to executive functions. However, the precise nature of these contributions is incompletely understood. We focused on a specific executive function, inhibition, the ability to suppress a pre-potent response. Functional imaging and animal studies have studied inhibition. However, there are only few lesion studies, typically reporting discrepant findings. For the first time, we conducted cognitive and neuroimaging investigations on patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
53
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 71 publications
9
53
1
Order By: Relevance
“…From this perspective, the increased rate of “yes responses” to BX trials in our cathode right DLPFC group could be interpreted as a consequence of an impairment in modulating the influence of dominant, integrated stimulus-response representations (“X-yes response”). It is worth noting here that while the two above-mentioned interpretations attribute distinct roles to the right DLPFC, both fit well with the general assumption that this region is a core component of the inhibitory control network (i.e., Kelly et al, 2004; Shackman et al, 2009; Gagnepain et al, 2014; Zmigrod et al, 2014; Cipolotti et al, 2016), which could have been compromised by cathodal tDCS in the present experiment.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…From this perspective, the increased rate of “yes responses” to BX trials in our cathode right DLPFC group could be interpreted as a consequence of an impairment in modulating the influence of dominant, integrated stimulus-response representations (“X-yes response”). It is worth noting here that while the two above-mentioned interpretations attribute distinct roles to the right DLPFC, both fit well with the general assumption that this region is a core component of the inhibitory control network (i.e., Kelly et al, 2004; Shackman et al, 2009; Gagnepain et al, 2014; Zmigrod et al, 2014; Cipolotti et al, 2016), which could have been compromised by cathodal tDCS in the present experiment.…”
Section: Discussionsupporting
confidence: 80%
“…The right DLPFC, along with other prefrontal and subcortical regions, is typically considered a part of an inhibitory network (Kelly et al, 2004; Beeli et al, 2008; Shackman et al, 2009; Gagnepain et al, 2014; Cipolotti et al, 2016; but see Aron et al, 2014). Thus, for example, this region is thought to play a role in the distributed neural system underpinning behavioral inhibition in response to threat, with more behaviorally inhibited individuals showing more EEG activity in the right DLPFC (McNaughton and Corr, 2004; Shackman et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similar increases in inhibitory control, revealed as faster responses to incongruent word-color conditions, have also been encountered after high-frequency rTMS over left dlPFC (Vanderhasselt et al, 2006 ; Kim et al, 2012 ). The left dlPFC is directly involved in inhibitory control processes (Miller and Cohen, 2001 ; Cipolotti et al, 2016 ), thus the increased excitability of this region can lead to a better performance. Nonetheless, in our study, the excitability decrease hypothetically caused by cTBS (Tupak et al, 2013 ) did not hinder the capacity for inhibitory control, unlike in a previous study (Lowe et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…This “paradoxical facilitation” after decreasing cortical excitability could be explained by a disruption of a competing process localized in the left hemisphere, probably causing a transcallosal facilitation in the contralateral region. Indeed, different studies show the involvement of the right dlPFC in planning abilities, visuospatial memory, and/or response inhibition, the three main processes measured by the Tower of Hanoi (Epstein et al, 2002 ; Fincham et al, 2002 ; Sack et al, 2005 ; Srovnalova et al, 2012 ; Kaller et al, 2013 ; Fried et al, 2014 ; Cipolotti et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Roca et al (2010) demonstrated that impaired performance in frontal patients on EF tests such as the Wisconsin Card Sorting Test, verbal fluency and the Iowa Gambling Task can be explained by fluid intelligence impairments, although Robinson et al (2012) showed the opposite for verbal fluency. However, for other EF tasks such as the Hayling Sentence Completion test and the Stroop test, frontal patients' impairments could not be accounted for by reduced fluid abilities (Roca et al, 2010;Cipolotti et al, 2016: for a similar finding in schizophrenia see Martin et al, 2015). Moreover, although Barbey et al (2012) identified shared neural substrates in the frontal and parietal cortex for EF and general intelligence (g), there were additional brain regions specific to EF (e.g., the left anterior pole) and brain regions specific to g (e.g., the left inferior occipital gyrus and the right superior and inferior parietal lobe).…”
Section: Intelligence and Efmentioning
confidence: 99%